2005
DOI: 10.1002/ps.1119
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal spider venom toxin fused to snowdrop lectin is toxic to the peach‐potato aphid, Myzus persicae (Hemiptera: Aphididae) and the rice brown planthopper, Nilaparvata lugens (Hemiptera: Delphacidae)

Abstract: The SFI1/GNA fusion protein, comprising of snowdrop lectin (Galanthus nivalis agglutinin, GNA) fused to an insecticidal spider venom neurotoxin (Segestria florentina toxin 1, SFI1) was tested for toxicity against the rice brown planthopper Nilaparvata lugens (Stål) and the peach-potato aphid Myzus persicae (Sulzer) by incorporation into artificial diets. Significant effects on the mortality of N. lugens were observed, with 100% of the insects fed on the SFI1/GNA fusion protein diet dead by day 7. The survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 36 publications
1
42
0
1
Order By: Relevance
“…Sadeghi et al (2009a) reported an LC50 value for GNA of 350 µg mL -1 for pea aphids, which is about three times more than what is required in the current study to kill the same percentage of aphids. Down et al (2006) reported < 10% mortality of M. persicae after 14 d exposure to diet containing 1.4 g L -1 of GNA lectin. The response of each species of aphid to phytochemicals was quite different.…”
Section: Discussionmentioning
confidence: 99%
“…Sadeghi et al (2009a) reported an LC50 value for GNA of 350 µg mL -1 for pea aphids, which is about three times more than what is required in the current study to kill the same percentage of aphids. Down et al (2006) reported < 10% mortality of M. persicae after 14 d exposure to diet containing 1.4 g L -1 of GNA lectin. The response of each species of aphid to phytochemicals was quite different.…”
Section: Discussionmentioning
confidence: 99%
“…One of the proteins used is a lectin, which functions as a carrier (GNA, Galanthus nivalis agglutinin) and the other protein is a toxin. A fusion protein comprising GNA and SFI1 has been shown to have insecticidal effects on both lepidopteran and homopteran plant pests (Fitches et al, 2004;Down et al, 2006) while a fusion protein combining GNA with ButaIT has also been shown to have insecticidal activity against lepidopteran larvae. The injection data reported show that fusion proteins containing SFI1 and ButalT are insecticidal towards a range of insects including lepidopteran, dipteran, coleopteran and dictyopteran pests (Fitches et al, 2010).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Consequently, GNA has been exploited as a transporter for several different insecticidal toxins (Fitches et al, 2001;Fitches et al, 2004;Down et al, 2006;Trung et al, 2006;Wakefield et al, 2006;Fitches et al, 2012). GNA itself is weakly insecticidal in some insect species, but not as potent as insecticidal spider toxins.…”
Section: Discussionmentioning
confidence: 99%
“…GNA has been used to improved the oral activity of a variety of insecticidal neurotoxins (Fitches et al, 1997;Fitches et al, 2001;Fitches et al, 2002;Fitches et al, 2004;Down et al, 2006;Trung et al, 2006;Wakefield et al, 2006;Fitches et al, 2010;Wakefield et al, 2010;Fitches et al, 2012). GNA and CP both bind to receptors in the insect gut and subsequently cross the epithelium by transcytosis (Fitches et al, 1997;Fitches et al, 2001;Fitches et al, 2012;Bonning and Chougule, 2014; .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation